The effect of democratic leadership style on executive decision making at Petroliam Nasional Berhad (PETRONAS) / Muhammad Faiz Mat Jelan and Syed Ashraaf Wan Mohamad - Mat Jelan, Muhammad Faiz; Wan Mohamad, Syed Ashraaf (Faculty of Business and Management, 2015)
This research was conducted to carry out a study entitled “The Effects of Democratic Leadership Style on Executive Decision Making”. The purpose of this study is to investigate the effect of power, organizational culture and commitment on executive decision making in PETRONAS Twin Towers. Besides that, it is to determine the rating of democratic leadership style and decision making. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine the rating of democratic leadership style and decision making and also to investigate the effect of power, organizational culture and commitment on executive decision making in PETRONAS Twin Tower. For this study, executive level in PETRONAS Twins Towers was chosen as respondents. A questionnaire had been distributed to those who involved which are 341 respondents. The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS). From the correlation testing, the result shows Power has strong relationship, while Organizational Culture has moderate relationship and Commitment has very strong relationship. For the multiple regression analysis testing, the results indicate that power, organizational culture and commitment have proven that they are the factors that influenced decision making. For hypothesis, it shows that all independent variables which is power, organizational culture and commitment is supported. This study suggested management of PETRONAS Twin Towers to more concern on the most significant variable which is commitment that can effect on executive decision making, while for future researcher to widen scope of respondent and increase the number of variables.